The Role of Elementary School Teachers in Implementing the Curriculum - Siswiyatiningsih Siswiyatiningsih; Wahid Murni; Samsul Susilawati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines the role of Madrasah Ibtidaiyah teachers in curriculum implementation as a crucial component of the national education system. Teachers play a strategic role in determining the success of curriculum implementation through their direct involvement in teaching and student character development. This study employs a library research method by reviewing books, scientific journal articles, previous studies, and official curriculum-related documents. The collected data were analyzed using a qualitative descriptive approach through data collection, reduction, categorization, and interpretation. The findings indicate that Madrasah Ibtidaiyah teachers serve as curriculum designers, implementers, and evaluators. Beyond delivering subject content, they are responsible for integrating Islamic values with general knowledge to foster holistic learning. Teachers are also expected to apply creative, innovative, and student-centered instructional strategies to achieve curriculum objectives effectively. The success of curriculum implementation is influenced by teachers’ pedagogical, professional, social, and personal competencies, as well as supporting factors such as educational facilities, the school environment, and institutional policies. Therefore, strengthening teacher professionalism through continuous training, academic mentoring, and institutional support is essential to improving curriculum implementation and enhancing the quality of national education